Assessment of etching and optical characteristic of an indigenously prepared poly allyl diglycol carbonate solid-state nuclear track detector material on gamma irradiation and its applicability in gamma dose measurements - Jyotsna Sapkal (Radiation Protection and Environment)
Studies were conducted to assess the effects of high intensity γ radiation on the etching and optical parameters of an indigenously prepared polyallyl Diglycol carbonate (PADC) polymer by using well-known UV – Visible and FTIR spectroscopic techniques. Polycarbonate detectors were exposed to different gamma exposures ranging from 10 – 430 kGy using a pre calibrated 60Co gamma chamber. The bulk etch rates were estimated at different temperatures. The activation energy for the bulk etching of PADC material was determined for different doses. It is observed that the bulk etch rates increases and the activation energies for the bulk etching decreases with the increase in gamma dose. The optical absorption energies (Eg) were analyzed using recorded UV–Visible spectra, and it was observed that the Eg values decreased with increasing gamma exposures. Gamma irradiation generates free radicals, leading to chain scission in the longer carbonate links of the polymer detector. This process reduces the absorption (Eg) values. Variation in absorbance with different gamma doses were also studied using FTIR technique and it was found that the transmission (T) changes with the gamma irradiation doses. These results have been explained on the basis of scission of the detector due to gamma irradiation. The present studies can be used for the estimation of gamma dose in the range of 10 – 430 kGy. The results were compared with commercially available imported CR-39 polymer detectors.